PENGARUH POLA ASUH NEGLECTFUL ORANG TUA TERHADAP EMPATI SISWA DI SMP NEGERI 21 SAMARINDA TAHUN AJARAN 2024/2025 - Apryana Wulandari; Dwi Sona; Wahyu Widyatmoko; Anggraeni Swastika Sari (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study was motivated by the low level of empathy among students at SMP Negeri 21 Samarinda, as revealed by preliminary observations and interviews. The study aimed to determine whether neglectful parenting patterns had an effect on student empathy at SMP Negeri 21 Samarinda. It used a quantitative approach with an ex-post facto research design. The population in this study consisted of 67 students from grades 7 and 8 who were obtained from the results of a screening test. The sample in this study used a saturated sample. The data analysis technique in this study used a simple linear regression test with the help of SPSS for Windows version 26. The results showed that F = 30.406 > 3.99 with Sig. 0.000 < 0.05, so H_a was accepted. The results proved that there was a significant effect of neglectful parenting on empathy, with a regression coefficient of -0.353, indicating a negative effect. This means that the higher the neglectful parenting pattern, the lower the empathy among students at SMP Negeri 21 Samarinda. Conversely, the lower the neglectful parenting pattern, the higher the empathy among students at SMP Negeri 21 Samarinda.